Fenomena Calon Tunggal dalam Pesta Demokrasi - Iza Rumesten RS (The Constitutional Court of the Republic of Indonesia, 2016)
Concurrent local elections to be held in December 2015, characterized by the dynamics of democracy and new political dynamics. Dynamics it is the birth of a single candidate in several areas that will carry out the election. It is on the one hand shows that the dynamics of democracy in the country increasingly show progress and our society is increasingly “literacy” and political savvy, but on the other hand it raises a new problem, namely whether the elections will be postponed or published decree. This happens because the legislators did not expect the birth of a single candidate. This fact shows that the lawmakers have not been able to make laws that meet the philosophical and sociological aspects of that legislation was well received presence in the midst of society without conflict and live longer. Because it is common to occur in Indonesia legislation only whole corn.Issues to be addressed in this study is what legal remedies in the face of a single candidate and how the legal steps to prevent the birth of a single candidate in the elections. This study is a normative legal research, using qualitative juridical analysis. The result showed that the legal solutions that can be done to deal with a single candidate is to 1). Exposes a single candidate with an empty tube, 2). Delay the election until the election outright in 2017. 3). Published the decree. While the legal steps that can be taken to prevent the birth of a single candidate is 1. Revise election laws, by adding specific chapter or article concerning a single candidate, 2. Increasing political education for the public and political party cadres and prepare the mature cadre in the party’s internal.